(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Introduzione - 2. Linguaggio, discorso e ragione - 3. Linguaggio ordinario e linguaggi esperti - 4. Linguaggio e sfera pubblica - 5. La teoria del discorso e le tradizioni religiose: alcuni cenni sul pensiero di Habermas - 6. Il fondamentalismo religioso - 7. La “traduzione neutralizzante” - 8. Conclusioni. Religion and public sphere in Jürgen Habermas’s discoursive theory ABSTRACT: The relationship between religion and the public sphere, from the perspective of Habermas’s theory of discourse, gives a glimpse of the possibility of a shared space, reflected in democratic decision-making procedures, which has priority over every strategic and self-referential representation of the social. The "linguisticization of the sacred" process has gradually led the author to free the theory of modernity from a rigid theory of secularization; on the other hand, the religious phenomenon, freed from obsolete dogmatisms, reveals itself as the bearer of a procedural rationality capable of operating in everyday communication practice. In this dialogic path, which is anything but linear, Habermas’ communicative reason seeks to find solutions capable of safeguarding both religious dimensions and the legacy of Enlightenment thought. This, first of all, to stem the monological drift of particularistic global interests able to endorse, even in sectors of a public nature, dynamics typical of strategic-functional action that lead to the restriction of the common space and to the loss of effectiveness of the institutions traditionally deputies for the democratic representation of interests. At the resolution of these questions, the discursive reason does not offer a single answer but indicates a path of learning and constructive conciliation of the visions of the world.